Manipulation of facet orientation in hybrid perovskite polycrystalline films by cation cascade - Guanhaojie Zheng (Nature Portfolio, 2018)
Crystal facet orientations of the polycrystalline hybrid lead halide perovskite thin films play a crucial role in determining the device performance. Here Zheng et al. demonstrate effective control of the crystal stacking mode by cation cascade doping, which promotes the charge transport in the photovoltaic device.